2012
DOI: 10.1002/dmrr.2291
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators involved in the progression of the metabolic syndrome

Abstract: The metabolic syndrome is often associated with type 2 diabetes mellitus, dyslipidemia, atherosclerosis, hypertension, steatosis of the liver and other organs, as well as hypertension, type 2 diabetes mellitus, and atherosclerosis. Recent studies have implicated a number of inflammatory mediators including cytokines, adipokines and eicosanoids in the inflammatory responses that accompany the metabolic syndrome. Measurements of the circulating levels of the inflammatory molecules that accompany this syndrome mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 89 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…High-sensitivity C reactive protein (hsCRP) was measured by nephelometry on an IMMAGE analyser (Beckman-Coulter, Villepinte, France). We measured plasma levels of high-sensitive interleukin 6 level, reflecting global inflammation and ageing, soluble CD14 (sCD14) and soluble CD163 (sCD163) (Quantikine ELISA Kit, R&D Systems, Oxford, UK), two markers of monocyte/macrophage activation involved in HIV-related chronic immune activation,37 and leptin (Quantikine; R&D Systems, Oxford, UK) and total adiponectin (ALPCO, EUROBIO, Les Ulis, France), two adipokines involved in MetS38 39 and OA 40…”
Section: Methodsmentioning
confidence: 99%
“…High-sensitivity C reactive protein (hsCRP) was measured by nephelometry on an IMMAGE analyser (Beckman-Coulter, Villepinte, France). We measured plasma levels of high-sensitive interleukin 6 level, reflecting global inflammation and ageing, soluble CD14 (sCD14) and soluble CD163 (sCD163) (Quantikine ELISA Kit, R&D Systems, Oxford, UK), two markers of monocyte/macrophage activation involved in HIV-related chronic immune activation,37 and leptin (Quantikine; R&D Systems, Oxford, UK) and total adiponectin (ALPCO, EUROBIO, Les Ulis, France), two adipokines involved in MetS38 39 and OA 40…”
Section: Methodsmentioning
confidence: 99%
“…Leptin, resistin, and adiponectin originate predominately in adipose tissue (Rajala and Scherer 2003; Klempel and Varady 2011) and are known to contribute to the inflammatory milieu (Ma et al. 2012). While leptin and resistin are positively correlated with body mass index (Friedman 2002; Pagano et al.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of celecoxib was then stopped, and the FBG levels rebounded to 6.9±0.4 and 7.1±0.1 mmol/l in approximately 3 days, respectively. Nevertheless, the influence (Table 3) [13][14][15]. We found that 238 differentially expressed secretory genes were inflammatory mediators and the number was about half that of the differentially expressed secretory genes (ESM Table 4).…”
Section: An Inflammatory Mediator Of Inflammation (Tnfsf13) Is Correlmentioning
confidence: 95%